Students’ Perception of Using Instagram Learning Account Towards Their Vocabulary Mastery - Arun, Hetfil; Nugraeni, Ismawati Ike; Johan, Andrian Nuriza (Universitas Muhammadiyah Mataram, 2025)
This study investigates the perceptions of junior high school students on the use of Instagram learning accounts to support their English vocabulary acquisition. The research used descriptive quantitative design with a survey approach. The data were collected from 112 ninth grade students at SMP Negeri 12 Purworejo through a closed-ended questionnaire based on cognitive, affective, and conative aspects. The results showed that in general, students have a high perception of the role of Instagram in vocabulary development. The cognitive component received the highest mean score (M = 3.71), followed by the affective (M = 3.60) and conative (M = 3.59) components. Students perceived Instagram as a helpful, enjoyable, and convenient learning, with visual content significantly helping vocabulary comprehension and retention. In addition, students reported increased motivation, emotional engagement, and autonomy in vocabulary learning through the platform. These results shows that Instagram can aid as a valuable supplementary tool to support formal English language education, particularly in enhancing students' vocabulary acquisition.